2022
DOI: 10.32479/ijeep.12629
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition Factors Household Energy Subsidy Consumption in Indonesia: Kaya Identity and Logarithmic Mean Divisia Index Approach

Abstract: For decades, the subsidy had prompted excessive and wasteful while offering little motivation to boost energy efficiency or reduce domestic greenhouse gas emissions. This paper aimed to measure household subsidy energy by examining the relationship between the other ten variables. The Logarithmic Mean Divisia Index (LMDI) and decomposition index were deployed to recognize the determinant effects that drive household's subsidy energy consumption. This study also presented an ARDL model applied. The robustness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The priority, practicability, and environmental motivation are also essential factors that are widely discussed and are characteristics of conservatism energy adopters [7]. Numerous studies were driven by various variables, including environmental values and views that are society's moral duty to lower emissions, or in other words, as part of pro-environmental behaviour [8,9]. Environmental behavior is primarily tied to energy consumption and is defined as any action that contributes directly or indirectly to environmental conservation and sustainability [10].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The priority, practicability, and environmental motivation are also essential factors that are widely discussed and are characteristics of conservatism energy adopters [7]. Numerous studies were driven by various variables, including environmental values and views that are society's moral duty to lower emissions, or in other words, as part of pro-environmental behaviour [8,9]. Environmental behavior is primarily tied to energy consumption and is defined as any action that contributes directly or indirectly to environmental conservation and sustainability [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because so many technologies are used in our everyday lives and demand electricity, Indonesia's electricity usage is rising. The increase in electricity rates every year causes household costs also to increase [1]. One of the efforts to save is through cutting electricity consumption (curtailment) and replacing old equipment that requires a large amount of energy with new technology equipment that requires less energy or is energy efficient.…”
Section: Introductionmentioning
confidence: 99%
“…In the study, the Kaya identity was applied to analyse GHG emissions and their constituent components. The extended Kaya method was also widely applied in the analysis of carbon emissions and various aspects of urbanisation by other authors in different countries: energy efficiency by various sources [49], fossil fuel type [50], urbanisation effects [51], household energy consumption [52], agriculture sector [53]. Our study focuses on the effects of urbanisation ratio, urban population, and urban economic growth on GHG emissions.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The empirical found that obstacles to overcome in applying energy efficiency policy (Sudarmaji et al, 2021;2022;Dobbs et al, 2013;Gerarden et al, 2015;Schleich, 2012). Gerarden, Newell, and Stavins (2015) said there were two barriers, i.e., "market barriers" and "non-market barriers" in energy efficiency in neoclassical economics (O'Malley et al, 2003).…”
Section: Indonesian Population and Energy Consumptionmentioning
confidence: 99%